Treatment Patterns and Health Care Resource Utilization of Iatrogenic Spinal Cerebrospinal Fluid Leaks in the United States. Issue 9 (14th November 2022) - Charalambous, Lefko T.; Rajkumar, Shashank; Liu, Beiyu; Adil, Syed M.; Wong, Megan; Hodges, Sarah; Amrhein, Timothy J.; Leithe, Linda Gray; Parente, Beth; Lee, Hui-Jie; Lad, Shivanand P.
Abstract : Study Design: Retrospective cohort study. Objective: We aimed to characterize the treatment patterns and the associated costs in patients with cerebrospinal fluid (CSF) leak after spine procedures in the United States. Background: CSF leak is a common complication after spinal procedures. However, there is a little data regarding the national patterns of treatment choice and the associated health care resource utilization. Methods: We utilized the IBM MarketScan Research databases to retrospectively analyze adult US patients diagnosed with CSF leak within 30 days of spine procedures between 2001 and 2018. Treatment prevalence, treatment failure, and health care resource utilization data within 30 days of the CSF leak were collected. A subanalysis was performed on patients who received epidural blood patches (EBP) to better understand health care utilization attributable to this treatment modality. Results: Twenty one thousand four hundred fourteen patients were identified. The most common causes of CSF leak were diagnostic spinal tap (59.2%) and laminectomy/discectomy (18.7%). With regard to treatment prevalence, 40.4% of the patients (n=8651) had conservative medical management, 46.6% (n=9987) received epidural blood patch repair, 9.6% required surgical repair (n=2066), and 3.3% (n=710) had lumbar drain/puncture. Nine hundred sixty-seven (9.7%), 150 (21.1%), and 280 (13.5%) patients failed initial EBP, lumbar drain, and surgery, respectively, and the overall failure rate was 10.9% (n=1397). The median 30-day total cost across all groups was 5, 101. Patients who received lumbar drain (22, 341) and surgical repair (30, 199) had higher 30-day median total costs than EBP (8, 140) or conservative management (17, 012). The median 30-day total cost for patients whose EBP failed (8, 179) was substantially greater than those with a successful EBP repair (3, 439). Conclusions: National treatment patterns and costs for CSF leaks were described. When used in the correct patient cohort, EBP has the lower failure rates and costs than comparable alternatives. EBP may be considered more often in situations where conservative management or lumbar drains are currently being used.